(untitled) (Bangladesh Journal of Medical Education, 2022)
In the history of human civilization, research has played a significant role. There is no doubt that meeting the challenges of the 21st century will be tough if we are not world leaders in science and technology. The objective of this study was to assess physicians’ attitude about research and the challenges they confront when doing research. From July to December 2020, a cross-sectional questionnaire survey was performed among physicians in Bangladesh. The questionnaire poll had 626 responses in total. There were 55.6 % female physicians and 44.4% male physicians among them. The majority of physicians (87.6%) felt that conducting research is critical to become a specialist. Research methodology training at the medical colleges are extremely beneficial, according to a substantial percentage of physicians (72.2%). Research methodology should be included in undergraduate curriculum, according to 89% of physicians. Research is beneficial as it aids critical thinking and policy implementation, according to almost all respondents (96.7%). The majority of respondents cited insufficient research training (92%), insufficient funding (92.2%), insufficient time (61%), insufficient familiarity with statistical analysis (88%), insufficient skill to design and conduct a research project and write a scientific paper (90%), as barriers to research. Priority on teaching and clinical practices over research and lack of interest to do research also mentioned by 93.3% and 61% responded respectively. Consequently, this study identified challenges and attitude of physicians towards research. This finding will guide for further studies to find out effective interventions to address the obstacles raised by research participants. Bangladesh Journal of Medical Education Vol.13(1) January 2022: 10-19